2002
DOI: 10.1063/1.1459598
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ti seed layer on the magnetization reversal process of Co/NiFe/Al-oxide/NiFe junction films

Abstract: Lorentz transmission electron microscopy and magnetic force microscopy characterization of NiFe/Al-oxide/Co films J. Appl. Phys. 91, 780 (2002); 10.1063/1.1427142 Effect of microstructure on the magnetoresistive properties of NiFe/Co(CoFe)/Al(Ta)-oxide/Co(CoFe) tunnel junctions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The presence of a few nanometers of Ti or Ti/TiO 2 layer reduces the nucleation activation energy between depositing material and substrate and influences the phase, orientation, crystallites and grain sizes [25,26]. Yu et al [27] has also shown that a Ti seed layer can enhance the structural quality of ferromagnetic films giving a strong texture and large grain size. Sreemany et al [28] and Millon et al [29] have reported that interface energy minimization occurs using a TiO x (x < 2) seed layer which results in the crystallization of highly oriented PZT films on Pt substrates.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of a few nanometers of Ti or Ti/TiO 2 layer reduces the nucleation activation energy between depositing material and substrate and influences the phase, orientation, crystallites and grain sizes [25,26]. Yu et al [27] has also shown that a Ti seed layer can enhance the structural quality of ferromagnetic films giving a strong texture and large grain size. Sreemany et al [28] and Millon et al [29] have reported that interface energy minimization occurs using a TiO x (x < 2) seed layer which results in the crystallization of highly oriented PZT films on Pt substrates.…”
Section: Resultsmentioning
confidence: 99%
“…The normal distribution of magnetic grains in the free layer was adopted. Each grain consists of a magnetic cubic cluster with the size of 20 nm  20 nm  4 nm: The validity and reliability of such a simulation method and its adopted parameters can be confirmed by a good fit to the main characters of the Lorentz transmission electron microscopy (LTEM) images of the MTJ magnetostructures under an electron beam, like a DC current, passing through the SBMTJ [20,21].…”
Section: Article In Pressmentioning
confidence: 99%
“…et al [5] thought Ti seed layer could induce a strong (111) texture in bottom of Co/NiFe bilayer, and domain wall mobility was higher due to strong crystallographic texture and large grain size in the bilayer; Mao, M et al [6] had deposited Ta/NiFe films respectively using ion beam deposition, pulse, static magnetron sputtering, and indicated that the high quality crystallization is the reason for excellent magnetic properties; Nakatani et al [7] had investigated the magnetoresistance effects and film structures in [Fe-Mn/Ni-Fe/Cu/Ni-Fe/buffer/Si] sandwiches with various substrate layer materials, and found that Nb, Ta, Ti, Zr or Hf substrate layer can cause strong (111) texture, which Cu, Ag, Au and Cr cannot; Choe,G. et al [8] had investigated the surface roughness' effect on magnetics properties of Ta/NiFe, and found in a wide range of thickness of NiFe (111) smooth substrate could yield higher anisotropy and lower coercivity; Sharp, RW et al [9] had made the multilayer Cr/NiFe films, and reported that due to the exchange anisotropy between antiferromagnetic material(Cr) and ferromagnetic material(NiFe), crystal anisotropy, magnetostriction etc.…”
Section: Introductionmentioning
confidence: 97%